HUBUNGAN ANTARA POLA SEKSUALITAS GRAVIDA DENGAN KETUBAN PECAH DINI - Tuti Meihartati (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
The rate of maternal mortality in Indonesia is still the highest in ASEAN which is 359 / 100,000 live births with premature rupture of membranes in Indonesia around 114 cases from all labor and maternal mortality due to premature rupture of membrane about 15 cases from all normal deliveries. This study aims to analyze the correlation between of gravida sexual pattern with premature rupture of membranes in Paradise Hospital Kecamatan Simpang Empat Kabupaten Tanah Bumbu. The method in this study was an analytical survey with cross sectional design. Sample were 46 pregnant women conducted by accidental sampling technique, and analyzed by Chi Square test. The results of the study obtained almost all (75.0%) of respondents who perform sexual patterns experience premature rupture of membranes. Statistical test obtained value p = 0,008 (<0,05). The conclusion of this study, there was significant correlation between sexual patterns with premature rupture of membranes. It is recommended for midwives to minimize the occurrence of premature rupture of membranes by providing communication, information, education to pregnant women how to perform good sexual patterns and frequency of the recommended sexual patterns.